Relationship between the age, the bone density, and the height of mandibular residual ridge in edentulous menopausal women - Aminah, Helmi Siti; Mahmud, Muslich; Rahajoeningsih, Poedji (Padjadjaran Journal of Dentistry, 2009)
Good quantity and quality of bones are keys to the success of prosthodontic treatment. The quantity of bones is showed by the height of mandibular residual ridge, whereas the quality of bones is indicated by the bone density.The aim of this study is to investigate the relationship between the age, the bone density, and the height of the mandibular residual ridge. The observation is carried out to six edentulous menopausal women. The height of mandibular residual ridge and the mandibular bone density are measured by using CBCT-3D (Cone Beam Computed Tomography-3 Dimension). Pearson analysis of bivariate correlation is used to determine the relation between variables. As a result, there is a strong correlation between the increased of the age and the decrease of mandibular bone density (r=-0.922 with α=0.009). The study also shows a significant correlation between the decrease of the height of mandibular residual ridge and the decrease of the mandibular bone density (r=0.815 with α=0.048) and between the decrease of the height of mandibular residual ridge and the increase of the age (r=-0.89 with α=0.017).To summarize, the decrease of the height of mandibular residual ridge in this study correlates with the decrease of the mandibular bone density and the age.